The cohesive zone crack analogue for fretting fatigue based on mild wear. (1st October 2022) - Giannakopoulos, A.E.; Zisis, Th.; Georgiadis, H.G.; Lindley, T.C.
Highlights: The modified crack analogue incorporates a novel cohesive zone at the contact edges of the original crack analogue model. The cohesive zone model introduces a new approach regarding the intimate synergy between friction and mild wear through plastic ratcheting of the surface asperities. The presented cohesive zone focuses on macroscopic fretting problems through the shear plasticity of the surface asperities (as mild wear). Similar cohesive zone models can be staged using dislocation plasticity, as well as atomistic and gradient elasticity models. Abstract: Fretting fatigue is an important problem that plagues many mechanical components that are in contact under vibrational loading. Life assessment of fretting fatigue cracking is important, with the damage initiation being difficult to estimate. This work extends a well-known fretting fatigue model, the crack analogue model that examines fretting induced by complete contacts or by adhering incomplete contacts of metallic surfaces. This is done by introducing cohesive zones at the contact edges. These zones address several issues related to friction and wear, by combining them in the case of mild wear where asperity plastic shearing is the dominant inelastic mechanism. Thus, the micromechanical behaviour of the surface topology is naturally introduced into the analysis. The surface roughness becomes an internal variable that evolves with the cyclic loading. The work of friction dissipates the mechanical energy and at the same time becomes the precursor of large scale wear. A predictive methodology for fretting crack nucleation is proposed through a novel cohesive model that incorporates friction and mild wear, lifting much pathology encountered by simple friction models at high normal loads.